Flavonoids in leaves of chestnut tree Aesculus hippocastanum L. as an indicator of ecological loading - Новза, Ю. А.; Попова, Е. М.; Вініченко, О. В. (Problems of Environmental Biotechnology, 2015)
The containing of flavonoids in the leaves of chestnut trees, gathered at the territories of airport Juliany and Hidropark of Kyiv were researched. It was established that the concentration of harmful substances influences on the containing of flavonoids in the leaves of chestnut trees. It was researched the level of air pollution on the territories of Hidropark and Juliany. It was established that the containing of flavonoids is growing with the increasing of containing of polluting substances in the air.